Signal Integration in Quorum Sensing Enables Cross-Species Induction of Virulence in Pectobacterium wasabiae - Rita S. Valente (American Society for Microbiology, 2017)
ABSTRACT Bacterial communities can sense their neighbors, regulating group behaviors in response to cell density and environmental changes. The diversity of signaling networks in a single species has been postulated to allow custom responses to different stimuli; however, little is known about how multiple signals are integrated and the implications of this integration in different ecological contexts. In the plant pathogen Pectobacterium wasabiae (formerly Erwinia carotovora), two signaling networks—the N-acyl homoserine lactone (AHL) quorum-sensing system and the Gac/Rsm signal transduction pathway—control the expression of secreted plant cell wall-degrading enzymes, its major virulence determinants. We show that the AHL system controls the Gac/Rsm system by affecting the expression of the regulatory RNA RsmB. This regulation is mediated by ExpR2, the quorum-sensing receptor that responds to the P. wasabiae cognate AHL but also to AHLs produced by other bacterial species. As a consequence, this level of regulation allows P. wasabiae to bypass the Gac-dependent regulation of RsmB in the presence of exogenous AHLs or AHL-producing bacteria. We provide in vivo evidence that this pivotal role of RsmB in signal transduction is important for the ability of P. wasabiae to induce virulence in response to other AHL-producing bacteria in multispecies plant lesions. Our results suggest that the signaling architecture in P. wasabiae was coopted to prime the bacteria to eavesdrop on other bacteria and quickly join the efforts of other species, which are already exploiting host resources. IMPORTANCE Quorum-sensing mechanisms enable bacteria to communicate through small signal molecules and coordinate group behaviors. Often, bacteria have various quorum-sensing receptors and integrate information with other signal transduction pathways, presumably allowing them to respond to different ecological contexts. The plant pathogen Pectobacterium wasabiae has two N-acyl homoserine lactone receptors with apparently the same regulatory functions. Our work revealed that the receptor with the broadest signal specificity is also responsible for establishing the link between the main signaling pathways regulating virulence in P. wasabiae. This link is essential to provide P. wasabiae with the ability to induce virulence earlier in response to higher densities of other bacterial species. We further present in vivo evidence that this novel regulatory link enables P. wasabiae to join related bacteria in the effort to degrade host tissue in multispecies plant lesions. Our work provides support for the hypothesis that interspecies interactions are among the major factors influencing the network architectures observed in bacterial quorum-sensing pathways.